Análise de políticas públicas: o Programa de Aquisição de Alimentos (PAA) em assentamentos rurais no município de Araras, estado de São Paulo - Villar, Gustavo Henrique do Lago (2017)
The evaluation of a public policy becomes important when it aims at important points within society, which is the generation of income for family agriculture in rural settlements and the acquisition and distribution of quality food for people at risk of food and nutritional assistance Institutions. The research had as general objective the evaluation of the PAA in the rural settlements of Araras, demonstrating the effectiveness and social cohesion and the relation of agroecology in the productive processes of these families. In this sense, the specific objectives were to analyze the quality of life and the change provoked in the productive matrices within the lots analyzed. As a theoreticalmethodological reference, this research was based on the work of scholars of neo-institutionalism in order to understand the role of institutions in the behavior of individuals affected by public policy. The data presented were obtained by questionnaires previously elaborated with information taken from the field diaries, as a methodological tool contributed to a better refinement of the discussions among the researchers. With this, we conclude that the PAA did not reach all the settlements located in Araras in an egalitarian way and does not fulfill some proposed objectives within its scope. There was no change to a significant organic productive matrix provoked by the access to the program, demonstrating a low effectiveness, just as there was no incorporation of one of the settlements due to lack of structure and disbelief in public institutions and social organization, which characterizes little social cohesion.